Clinical efficacy of romosozumab in the treatment of elderly male patients of osteoporotic with hip fractures: a retrospective study - Yichao Ji; Fan Zhang (Journal of Men's Health)
Background: This study aims to evaluate the efficacy and safety of romosozumab in elderly male patients with osteoporosis-associated hip fractures. Methods: A retrospective analysis was conducted using medical records from 94 elderly male patients with hip fractures who received treatment at our institution between October 2021 and March 2023. The patients were divided into two groups based on their treatment regimens: the observation group (n = 47) received monthly subcutaneous injections of 210 mg romosozumab for 12 months, and the control group (n = 47) was administered 10 mg of alendronate sodium orally each morning. Results: The results showed that the total effective rate was significantly higher in the observation group (p < 0.05), with a marginally greater rate of significant effectiveness in the observation group. Post-treatment assessments indicated significantly lower Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) scores in the observation group than the control group (p < 0.05). Bone mineral density (BMD) in the observation group was markedly higher, with significantly reduced levels of osteocalcin (OSC) and bone-specific alkaline phosphatase (BALP) (p < 0.05). Quality of life scores improved significantly in the observation group (p < 0.05), and there was no significant difference in adverse event incidence between the two groups (p > 0.05). Follow-up evaluations at 3, 6 and 12 months revealed that the observation group maintained higher BMD, osteocalcin, procollagen type 1 N-terminal propeptide (P1NP), and C-terminal telopeptide of type 1 collagen (CTx) levels, alongside a reduced incidence of fractures and adverse events compared to the control group (p < 0.05). After one year, the fracture healing rate was significantly higher in the observation group (p < 0.05). Conclusions: These findings suggest that romosozumab provides a substantial therapeutic benefit in elderly male patients with osteoporotic hip fractures, with no notable increase in adverse reactions and favorable follow-up outcomes.